An Analysis of Nahwu Learning Difficulties among Students of Zainul Hasan Genggong Islamic Boarding School - Muhammad Hawal Sholeh; Edi Kurniawan Farid; Ainur Rofiq Sofa (Al-Muyassar: Journal of Arabic Education, 2025)
This study aims to analyze the difficulties in learning Nahwu among the students of Pondok Pesantren Zainul Hasan Genggong. Nahwu, as one of the branches of Arabic linguistics, plays a crucial role in understanding Islamic texts, particularly the Qur'an and Hadith. However, many students face challenges in learning Nahwu, which can hinder their comprehension of Islamic teachings.This research employs a qualitative approach with a descriptive method to explore the factors contributing to the difficulties in learning Nahwu among the students at Pondok Pesantren Zainul Hasan Genggong. Data were collected through interviews with teachers and students, as well as observations of the learning process at the pesantren.The findings indicate that the main difficulties faced by students include a lack of fundamental understanding of Nahwu rules, limited time to study the material in depth, and less interactive teaching methods. Additionally, students' motivation and interest in Nahwu lessons also play a significant role in determining the level of difficulty they experience. Based on these findings, it is recommended to enhance teaching methods to be more interactive and to develop learning strategies that can facilitate students' understanding of Nahwu more effectively.Keywords: Learning Problems, Nahwu, Students, Pesantren, Problem Solving.  مستخلص البحثيهد? هذا البحث إلى تحليل مشكلات تعلم النحو لدى طلاب معهد زين الحسن قنقونج. يعتبر النحو، كأحد ?روع اللغة العربية، ذا أهمية كبيرة ?ي ?هم النصوص الإسلامية، خاصة القرآن الكريم والحديث النبوي. ومع ذلك، يواجه العديد من الطلاب صعوبات ?ي تعلم النحو، مما قد يعيق ?همهم للتعاليم الإسلامية. يستخدم هذا البحث المنهج النوعي مع الأسلوب الوص?ي لاستكشا? العوامل التي تسبب مشكلات تعلم النحو لدى طلاب معهد زين الحسن قنقون. تم الحصول على البيانات من خلال المقابلات مع المعلمين والطلاب، بالإضا?ة إلى ملاحظة عملية التعلم ?ي المعهد. أظهرت نتائج البحث أن المشكلات الرئيسية التي يواجهها الطلاب تشمل قلة ال?هم الأساسي لقواعد النحو، ومحدودية الوقت لدراسة المواد بعمق، وطرق التدريس الأقل ت?اعلية. بالإضا?ة إلى ذلك، تلعب عوامل الدا?ع واهتمام الطلاب بدروس النحو دورًا مهمًا ?ي تحديد مستوى الصعوبة التي يواجهونها.بناءً على هذه النتائج، ي?قترح تحسين طرق التدريس لتكون أكثر ت?اعلية وتطوير استراتيجيات تعليمية يمكن أن تسهل ?هم الطلاب لمادة النحو بشكل أكثر ?عالية.الكلمات الم?تاحية: مشكلات التعلم، النحو، الطلاب، المعهد الإسلامي,حل المشكلات.